Bentuk Penyajian Tari Maanta Batanghari - Destrinelli, Destrinelli (Lembaga Yasin AlSys, 2023)
The purpose of this research is to explore the form of presentation of the Maanta Batanghari dance. In terms of clothing, music, property, movement and floor patterns. The method used in this research is descriptive analysis method using a qualitative approach. Data was collected through data collection methods, observation, interviews and documentation. Results and discussion concluded that. The form of the dance movement begins with the opening of the offering and continues with the delivery procession which is a sign of the completion of the ceremony between presenting the groom to the bride and groom. Furthermore, the flags at the ends contain money with various denominations from the lowest to the highest. Next is the silek movement and the last is the kneeling movement which is a procession and a form of receiving delivery offerings and the last is the closing offering movement by the emcee and music presenter.